37 Assessing Clinicians' Knowledge and Confidence Performing four Evidence-Based Practices in the NICU using the Neonatal Unit Clinician Assessment Tool. (October 2012) - Higman, W; Wallace, L; Blake, K; Law, S; Jackson, B
Abstract : The evidence that breast milk feeding reduces mortality and short and long-term morbidity among premature and small babies is well established but breastfeeding rates in neonatal units in the UK remain low. We present a case study of how a tertiary hospital unit with 100 staff undertook the Neonatal Unit Clinician Assessment Tool (NUCAT), an on-line objective knowledge test with ratings of confidence and knowledge in breastfeeding, breast milk expression, kangaroo care and positive touch knowledge and practices. Fifty one medical and nursing clinicians completed NUCAT. We report descriptive statistics (n=51), and paired t tests for pre-post knowledge test confidence items, and difference statistics (Chi squared and t tests or one way ANOVAs for establishing differences in knowledge and confidence (Dependent Variables) on personal descriptive variables (Independent Variables).Confidence in knowledge was significantly reduced when individuals received their scores, but confidence in breastfeeding practice was not reduced. More staff scored better on the practical than knowledge based areas. Doctors, those with more neonatal experience and years since qualifying were not more knowledgeable than other clinicians overall, but clinicians with more senior positions knew more about the knowledge underpinning breastfeeding practices. Data reported include regression of job type, prior training, years since qualified, years working in neonatal care, intensity of direct care duties, on knowledge and confidence scores which help to target future training on those with most urgent job requirements for these practice skills. Training recommendations are discussed.